دور معايير إدارة جودة التدقيق في دعم حوكمة الشركات - عبلة بوزيد; زهرة خلف (university of eloued جامعة الوادي, 2025)
"امللخص هتدف هذه الدراسة إىل حتليل دور معايري إدارة جودة التدقيق يف دعم حوكمة الشركات، وذلـ سسـتادام املـجها الويـدي ودراسـة اربالـة عـم اسـتبيان مـو علـ 57 مـم مـدققي اربسـاست، احملـااء ، اسـما احملاسـبي ، وأساتذة التاصص. أظهرت الجتائا وجود عالقـات إااييـة ذات داللـة إحصـائية يـ التـ ام مكاتـت التـدقيق يتطبيـق 1 ISQM واعاليـة أمءمـة اةـودة ايهـا، ويـ دعـم اربوكمـة. كمـا تبـ أن اسـتادام ميشـرات جـودة التـدقيق يعـ ـال وةـان التـدقيق القوي ـة يرتبطـان ـودة التـدقيق، ـا يسـاهم يف دة قـ حوكمـة الشـركات، وأن اااصـا الدع املستثمريم، والكشف عم املمارسات االحتيالية، وحتس الرقاية الداخلية يف امليسسات. "This study aims to analyze the role of audit quality management standards in supporting corporate governance, using a descriptive approach and a case study based on a questionnaire distributed to 75 auditors, accountants, accounting experts, and academic specialists. The results revealed statistically significant positive relationships between the application of ISQM 1 by audit firms and the effectiveness of their quality systems in enhancing governance. The use of audit quality indicators was found to strengthen corporate governance, while effective disclosure and strong audit committees were linked to higher audit quality, increased investor confidence, detection of fraudulent practices, and improved internal control Keywords: Audit Quality, Audit Quality Management, Audit Quality Management Standards, Corporate Governance."
ماستر
Keywords: جودة التدقيق; إدارة جودة التدقيق; عايري إدارة جودة التدقيق،; حوكمة الشركات; Audit Quality; Audit Quality Management; Audit Quality Management Standards; Corporate Governance.